Readings for the Crisis in Feminist Key: a Comparison of Literature Regarding the Specific Effects on Women - Agenjo Calderón, Astrid (Papeles de Europa, 2011)
This paper seeks to identify how the crisis affects specifically to women, understanding that this depends on the different position they take in the socioeconomic system with respect to men, as a result of unequal power they have. For this, we use a comparison of the literature specialized in placing those power relations between genders as priority area of theoretical attention: this is, literature from Feminist Economics, differentiating between two streams - Feminist Economics of the Conciliation and Feminist Economics of the Ruptureand trying to identify the main similarities and differences in the analysis that they conducted in the crisis and its effects.
Keywords: Feminist Economics; Economic Crisis; Care Crisis